Policy on Free Land Provision for the Transmigration Development in Payahe Transmigration Area, Tidore City, North Maluku Province, Indonesia - Isra Muksin; Ida Widianingsih; Budhi Gunawan; Yogi Suprayogi Sugandi (Jurnal Manajemen Pelayanan Publik, 2022)
The purpose of this study was to determine the provision of free land for transmigration development, identify issues, constraints, challenges in implementing transmigration in the era of regional autonomy, formulate material for consideration policies among limited land for the future. The research applied qualitative; types of data required in this research were secondary and primary data. Main data in this research were in the form of transmigration area development planning documents, regulations and research reports. The results of the study found that people who were at the transmigration development site gave their land for free to the local government accompanied by a report of the handover an area of 4 hectares. The novelty of this research focuses on the policy of providing free land in Payahe transmigration area to gain community support and participation without causing conflict of interest so that the development of the transmigration area can proceed smoothly. The analysis process is focused on aspects of policies and strategies for providing land supply processes and mechanisms, constraints and challenges, and the impact of transformation of land provision policies. Based on the results of the data analysis, it will be grouped and formulated as policy information for the formulation of policies for the provision of transmigration land.